2014
DOI: 10.1136/postgradmedj-2012-131679
|View full text |Cite
|
Sign up to set email alerts
|

Continuous professional development for GPs: experience from Denmark

Abstract: Danish GPs are frequent users of voluntary accredited CPD. Their CPD choices are motivated by topics strengthening their professional capacity and preventing burnout. There would seem to be no need for a mandatory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…11 Patient-related clinical problems encountered in general practice, lack of confidence in certain aspects of practice and interest in learning new knowledge can provide motivation for CE activities. 24 In the present study, an improvement in the motivation for learning was one of the most commonly reported (79.8%) effectiveness of CE programmes. It is encouraging to observe that the majority of dentists perceived that their motivation for learning increased as a result of CE courses.…”
Section: P-value Adjusted or (95% Ci)supporting
confidence: 57%
“…11 Patient-related clinical problems encountered in general practice, lack of confidence in certain aspects of practice and interest in learning new knowledge can provide motivation for CE activities. 24 In the present study, an improvement in the motivation for learning was one of the most commonly reported (79.8%) effectiveness of CE programmes. It is encouraging to observe that the majority of dentists perceived that their motivation for learning increased as a result of CE courses.…”
Section: P-value Adjusted or (95% Ci)supporting
confidence: 57%
“…27 Sometimes they are unaware of those gaps and , without an ability to identify them, cannot act accordingly. This is a vital feature of the Johari window and the ability to recognise unknown gaps in knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…CME is essential for GPs to keep abreast of the latest chronic disease management practices and serve as a platform to exchange experiences with their colleagues [65]. In addition, PCN leaders are no longer only the captain of their practice but gatekeeper of the entire network.…”
Section: Discussionmentioning
confidence: 99%